Network of CoPs between extensionists, scientists, and farmers to optimize capacity building: Elaboration and implementation of capacity development plan - Diaz Espinosa, Anabell; García Santiago, Jorge O.; Martínez, Oscar; Leal Gonzalez, Abel J.; Loon, Jelle van (Bioversity International and the International Center for Tropical Agriculture, 2023)
As part of the process to strengthen the capacities of local stakeholders and facilitate the adoption of sustainable practices, from within the context of the Innovahubs a comprehensive training strategy was designed and put into action. The methodology implemented for this purpose consists of two main blocks: i) Planning (based on the identification of topics of interest for technical advisors and key partners in each of the Innovahubs, ii) Implementation of the training plan oriented to practical application, including face-to-face and distance training events and iii) monitoring and evaluation, which focused on practical and summative evaluation. This resulted in training events where network members were able to identify the scope of the Resilient AgriLAC Initiative, strengthen their capacities and develop new ones through theoretical learning and exchange.